Keamanan Personal Masyarakat Sipil dalam Konflik Bersenjata: Kegagalan Perlindungan Internasional pada Blokade Koridor Lachin (2022–2023) - Wafa Wafa; Abdullah Abdullah (Indonesian Social Science Review, 2026)
This study examines the limitations of personal security protection for civilians in situations of armed conflict, focusing on the Lachin Corridor Blockade of 2022–2023. The central problem addressed is the gap between the international normative recognition of human security and the realities of protection on the ground, which remain dominated by state sovereignty interests. This study aims to analyze the blockade's impact on the dimensions of individual security, identify the instruments of state sovereignty used to restrict humanitarian access, and evaluate the structural limitations of international protection mechanisms. The method employed is qualitative, using an explanatory case study design, with secondary data drawn from reports by international and humanitarian organizations, official documents, academic articles, and media coverage, analyzed through thematic analysis. The findings show that the blockade created systemic threats through structural physical violence, disruption of daily life patterns, and loss of confidence in the future for approximately 120,000 ethnic Armenian residents. The failure of protection stemmed from two mutually reinforcing mechanisms: the instrumentalization of sovereignty by Azerbaijan and the geopolitical paralysis of the Russian Peacekeepers in fulfilling their formal mandate. In conclusion, civilian protection within the international system remains fragile and dependent on the political will of sovereign states, underscoring a structural institutional failure in the implementation of the human security norm. Penelitian ini mengkaji keterbatasan perlindungan keamanan personal (personal security) masyarakat sipil dalam situasi konflik bersenjata, dengan fokus pada Blokade Koridor Lachin periode 2022–2023. Masalah utama penelitian ini adalah kesenjangan antara pengakuan normatif terhadap human security secara internasional dan realitas perlindungan di lapangan yang masih didominasi kepentingan kedaulatan negara. Penelitian ini bertujuan menganalisis dampak blokade terhadap dimensi keamanan individu, mengidentifikasi instrumen kedaulatan negara yang digunakan untuk membatasi akses kemanusiaan, serta mengevaluasi keterbatasan struktural mekanisme perlindungan internasional. Metode yang digunakan adalah kualitatif dengan desain studi kasus eksplanatif, menggunakan data sekunder dari laporan lembaga internasional dan kemanusiaan, dokumen resmi, artikel akademik, serta pemberitaan media, yang dianalisis melalui teknik analisis tematik. Hasil penelitian menunjukkan bahwa blokade menciptakan ancaman sistemik melalui kekerasan fisik struktural, disrupsi pola hidup sehari-hari, dan hilangnya kepastian masa depan bagi sekitar 120.000 penduduk etnik Armenia. Kegagalan perlindungan bersumber dari dua mekanisme yang saling memperkuat: instrumentalisasi kedaulatan oleh Azerbaijan dan kelumpuhan geopolitik Russian Peacekeepers dalam menjalankan mandat formalnya. Kesimpulannya, perlindungan masyarakat sipil dalam sistem internasional bersifat rapuh dan bergantung pada kehendak politik negara berdaulat, menegaskan adanya kegagalan institusional struktural dalam implementasi norma human security.